Refining the link between psychopathy, antisocial behavior, and empathy: A meta-analytical approach across different conceptual frameworks - Campos, Carlos (2022)
The current meta-analysis includes 477 records (N = 142,692) and comprehensively explores the complex interplay between psychopathy, antisocial behavior, and empathy. First, empathy domains (cognitive and affective) were used to dissociate antisocial behavior from psychopathy. Cognitive empathy was more impaired in antisocial groups (gcognitive = -0.43; gaffective = -0.11), while samples scoring higher in psychopathy displayed larger deficits in affective empathy (gaffective = -0.40; gcognitive = -0.22). Secondly, the specific associations between empathy domains and psychopathy dimensions were evaluated. Most effect sizes pertaining to psychopathy traits closely related to antisocial behavior were mild for both empathy domains (r = -0.03 to -0.21). Callous-affective traits were largely correlated with affective empathy (r = -0.34 to -0.46) and moderately correlated to cognitive empathy (r = -0.26 to -0.27). Diverging results were found for the interpersonal dimension, as boldness-adaptive manifestations were unrelated to cognitive empathy (r = 0.03), while non-adaptive interpersonal traits were negatively associated with both empathy domains (rcognitive = -0.16; raffective = -0.25). Overall, these findings suggest that: (1) psychopathy and antisocial behavior display distinct empathic profiles; (2) psychopathy dimensions are differentially associated with cognitive and affective empathy; (3) the interaction between interpersonal traits and empathy domains is different across the conceptual models of psychopathy. Keywords: psychopathy; personality; antisocial; empathy; theory of mind; social cognition